Implementation of the Reading Aloud Method in Improving Learning Outcomes on Halal and Haram Food Material at Nurullah Cirebon Private Elementary Madrasah - Setiawan, Wawan; Waridin; Sukarsih, Winda; Yantika, WindI; Febrianti, Winda (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to determine the application of the Reading Aloud method in improving learning outcomes of halal and haram food material for 6th grade students at MIS Nurullah Cirebon. The Reading Aloud method was chosen because it can help improve students' understanding of the material being taught, by involving reading aloud techniques that facilitate listening and repetition of information, so that students can more easily understand and remember the material. This study uses a quantitative approach with a classroom action research (CAR) design. The subjects of the study consisted of 16 6th grade students who were divided into two learning cycles. The instruments used in this study were learning outcome tests and observations. The results showed that the application of the Reading Aloud method can improve students' learning outcomes, both in terms of understanding the material on halal and haram food, as well as in speaking and listening skills. Students become more active in participating in the learning process because this method provides an opportunity to repeat and deepen their understanding. Significant improvements were seen in students' test results and communication skills. Based on these findings, it can be concluded that the Reading Aloud method is effective in improving learning outcomes of halal and haram food material at MIS Nurullah Cirebon.